Hukum yang Dipergunakan dalam Kontrak Dagang Internasional - Anindita, Sri Laksmi (UI Scholars Hub, 2008)
International business contract basically is an agreement between two or more parties which has certain commercial value, where there is a foreign element. Nevertheless, the party in the international business contract has to be a legal entity which has the capability to act before the law. Furthermore, drafting an international business contract should not breach the regulation that govern the parties and formal regulation as where the contract is signed and prevailed. In an international business contract, it is common to mention the dispute settlement mechanism and the choice of law which will be used if a dispute arises. The common mechanism that is used is arbitration. However, the principle of Pacta Sunt Servanda, should not put aside the prevailing laws. Even though the contract stated that the parties has chosen arbitration as the mechanism for the dispute settlement, however if a party wish to file a bankruptcy petition, it should be filed to the bankcruptcy court and use the Bankcuptcy Act.